PEMBERIAN PROBIOTIK DENGAN DOSIS BERBEDA TERHADAP PERTUMBUHAN IKAN BAUNG (Mystus nemurus) - Rosyadi Rosyadi; Abdul Fatah Rasidi (DINAMIKA PERTANIAN, 2015)
The aims of this experiment were to find the effect of different doses of probiotics (raja siam) in a commercial feed on green catfish (Mystus nemurus) that is grown in freshwater pond. This experiment was conducted at the hatchery of Faculty of Aqriculture, Riau Islamic University, Pekanbaru. Twelve floating nets each size of 1x1x1.2 (m) were stocked with 10 individual of green catfish (Mystus nemurus). A completely randomized design with four treatments and three replications were used in this experiment. Four doses of probiotibs, i.e., 2 ml/kg (P1), 4 ml/kg (P2), 6 ml/kg (P3), and 0.0 ml/kg (P4) were used as treatment. The results showed that the best grouth of absolute body weight of green catfish was obtained in P1 treatment (34.67 gr), followed by P3 (32.67 gr), P2 (32.33 gr), and P0 (31.00 gr). The growth of absolute length for P1, P3, P2, and P0 treatment were 6.13 cm, 5.6 cm, 5.73 cm, and 5.33 cm, respectively, while the best daily growth rate was found at P1 treatment (1.62 , followed by P2 (1.52%), P3 (1.52), and P0 (1.50). Statistical analyses showed that there was not significant differences (P>0.05) across treatments. Fish feed conversion at the treatment P1, P2, P4, and P3 was 2.15; 2.26; 2.26 and 2.27, respectively. The average of survival rate was 100% and it was not significantly different (P>0.05).